Circle of Willis variation and outcome after intra-arterial treatment. Issue 2 (20th September 2022) - Rozeman, Anouk; Hund, Hajo; Boiten, Jelis; Vos, Jan-Albert; Schonewille, Wouter; Wermer, Marieke; Lycklama a Nijeholt, Geert; Algra, Ale
Abstract : Background: Intra-arterial treatment (IAT) improves outcomes in acute ischaemic stroke. Presence of collaterals increases likelihood of good outcome. We investigated whether variations in the circle of Willis (CoW) and contributing carotid arteries influence outcome in patients who had a stroke treated with IAT. Methods: CT angiography data on patients who had an acute stroke treated with IAT were retrospectively collected. CoW was regarded complete if the contralateral A1 segment, anterior communicating artery and ipsilateral posterior communicating artery were fully developed, and the P1 segment was visible. Carotid artery contribution was studied with a self-developed carotid artery score ranging from 0 to 2 depending on the number of arteries supplying the occluded side of the CoW. Good clinical outcome was defined as modified Rankin Score ≤2 and measured at discharge and 3 months. We calculated risk ratios for the relation between completeness of the CoW, carotid score and good outcome, and performed a trend analysis for good outcome according to the carotid score. Results: 126 patients were included for analysis. Patients with a complete and incomplete CoW had a comparable risk for good outcome at discharge and 3 months. A higher carotid score was associated with a higher likelihood of good clinical outcome (p for trend 0.24 at discharge and 0.05 at 3 months). Conclusion: In patients with acute ischaemic stroke treated with IAT, chances of good clinical outcome tended to improve with number of carotid arteries supplying the cerebral circulation. Completeness of the CoW was not related to clinical outcome.